Do Non-Monetary Incentive Systems Matter? Evidence From the Restructuring of a Non-Monetary Incentive System in an Online Community - Mutter, Tobias (Proceedings of the 21st European Conference on Information Systems (ECIS))

Towards an Agile Simulation-based Method for Creating, Evaluating and Selecting Business Models - John, Thomas; Weskamp, Christoph; Kundisch, Dennis; Suhl, Leena (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

Designing a Web-Based Classroom Response System - Kundisch, Dennis; Herrmann, Philipp; Whittaker, Michael; Neumann, Jürgen; Magenheim, J.; Reinhardt, W.; Beutner, Marc; Zoyke, A. (Proceedings of the Design Science Research in Information Systems and Technologies 2013 (DESRIST))

Does it Pay Off to Bid Aggressively? An Empirical Study - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Proceedings of the 46th Hawaii International Conference on System Sciences (HICCS))

Rekrutierung von Müttern mit Säuglingen in einer Interventionsstudie – erste Erkenntnisse aus der PINGU-Studie. - Mesch, C.; Stimming, M.; Wagner, A.; Libuda, Lars; Kersting, M. (Ernährungsumschau International)

Verfahrenstechnische Entwicklung zum Hinterspritzen von Echtholzfurnieren mit Wood-Plastic-Composites (WPC) - Schröder , Cathrin

Untersuchung des Prozessverhaltens neuartiger Einzugzonen-Konzepte für Kautschukextruder - Hallmann, Tobias

Prospective association of protein intake during puberty with body composition in young adulthood - Assmann, K.E.; Joslowski, G.; Buyken, Anette; Cheng, G.; Remer, T.; Kroke, A.; Günther, A.L.B. (Obesity)

Breastfeeding and Its Prospective Association with Components of the GH-IGF-Axis, Insulin Resistance and Body Adiposity Measures in Young Adulthood – Insights from Linear and Quantile Regression Analysis - Günther, Anke L. B.; Walz, Helena; Kroke, Anja; Wudy, Stefan A.; Riedel, Christina; von Kries, Rüdiger; Joslowski, Gesa; Remer, Thomas; Cheng, Guo; Buyken, Anette (PLoS ONE)

Adapting Hardware Systems by Means of Multi-Objective Evolution - Kaufmann, Paul
Reconfigurable circuit devices have opened up a fundamentally new way of creating adaptable systems. Combined with artificial evolution, reconfigurable circuits allow an elegant adaptation approach to compensating for changes in the distribution of input data, computational resource errors, and variations in resource requirements. Referred to as ``Evolvable Hardware'' (EHW), this paradigm has yielded astonishing results for traditional engineering challenges and has discovered intriguing design principles, which have not yet been seen in conventional engineering. In this thesis, we present new and fundamental work on Evolvable Hardware motivated by the insight that Evolvable Hardware needs to compensate for events with different change rates. To solve the challenge of different adaptation speeds, we propose a unified adaptation approach based on multi-objective evolution, evolving and propagating candidate solutions that are diverse in objectives that may experience radical changes. Focusing on algorithmic aspects, we enable Cartesian Genetic Programming (CGP) model, which we are using to encode Boolean circuits, for multi-objective optimization by introducing a meaningful recombination operator. We improve the scalability of CGP by objectives scaling, periodization of local- and global-search algorithms, and the automatic acquisition and reuse of subfunctions using age- and cone-based techniques. We validate our methods on the applications of adaptation of hardware classifiers to resource changes, recognition of muscular signals for prosthesis control and optimization of processor caches.

Plasma-polymerized HMDSO coatings to adjust the silver ion release properties of Ag/polymer nanocomposites - Alissawi, N.; Peter, T.; Strunskus, T.; Ebbert, Christoph; Grundmeier, Guido; Faupel, F. (JOURNAL OF NANOPARTICLE RESEARCH)
In the current work, we study the silver ion release potential and the water uptake through a SiOxCyHz-polymer which is grown from the precursor hexamethyldisiloxane (HMDSO) in radiofrequency (RF) plasma. These layers were deposited on top of two dimensional (2D) ensembles of silver nanoparticles (AgNPs) with nominal thickness of 2 nm on a 20 nm RF-sputtered polytetrafluoroethylene (PTFE) thin film. The composition of the plasma-polymerized HMDSO barriers was varied by changing the oxygen flow during the polymerization process and their thickness was varied as well. Morphology and optical properties of the nanocomposites were investigated using transmission electron microscopy (TEM) and UV-Visible spectroscopy (UV-Vis), respectively. The concentration of the silver ions released from the nanocomposites after immersion in water for several time intervals was measured using inductively coupled plasma mass spectrometry (ICP-MS). Contact angle analysis and electrochemical impedance spectroscopy (EIS) measurements were also performed and results show a strong dependence of the coatings properties and their water uptake on the oxygen content in the coating films and their thickness. Plasma polymerization with increasing the oxygen flow leads to the formation of more hydrophilic thin films with a higher Ag ion release potential. Increasing the thickness of the coatings reduced the amount of the released ions and the rate of the release process was slowed down. This indicates that by tailoring the structure and the thickness of the plasma-polymerized coating films, one can tune the silver ion release properties of Ag/polymer nanocomposites.

Goal-Scenario-Oriented Requirements Engineering for Functional Decomposition with Bidirectional Transformation to Controlled Natural Language. Case Study "Body Control Module" - Daun, Marian; Fockel, Markus; Holtmann, Jörg; Tenbergen, Bastian

Das Verteilungsproblem für mechatronische Systeme - Hüwe, Marcus

Simulationsgestützter Entwurf für Elektrofahrzeuge - Farshizadeh, Emad; Briese, Hermann; Steinmann, David; Stockmann, Lars; Beringer, Steffen; Holler, Dominik; Klobedanz, Kay; Heinzemann, Christian; Peter, Klaus; Leuer, Michael (8. Dortmunder Autotag)
Das Thema Elektromobilität hat in der Fahrzeugindustrie in den letzten Jahren viel Aufmerksamkeit erhalten. Gerade im Bereich der Entwicklung von Steuergeräte-Software ist der Bedarf an frühzeitiger Absicherung hoch. Nur so können Produkteinführungszeiten minimiert und effektiv Entwicklungskosten eingespart werden. Komplexe Werkzeugketten und die verteilte Entwicklung erschweren den Prozess und verlängern die Entwicklungszeit. Das Förderprojekt „Simulationsgestützter Entwurf für Elektrofahrzeuge“, kurz „E-Mobil“, nimmt sich der Herausforderungen einer verteilten Entwicklung von Steuergeräte-Software an. Vier Projektpartner aus Industrie und Forschung untersuchen die Besonderheiten sowohl bzgl. des Entwurfsprozesses, als auch der beteiligten Entwurfswerkzeuge im Vergleich zur konventionellen Fahrzeugentwicklung. Im Fokus stehen die Modellierung und die simulationsgestützte Absicherung in frühen Entwurfsstadien. Die Modellierung umfasst Regelungssoftware sowie die für die Simulation nötigen elektrischen und mechatronischen Komponenten. Die vorliegende Arbeit stellt die Kernthemen sowie aktuelle Ergebnisse aus dem Projekt vor.

Combining Scenario-based and Architecture-based Timing Requirements - Koch, Thorsten
Die in der Automobilindustrie verwendeten eingebetteten Systeme gehören zu den komplexesten eingebetteten Systemen. Die Automobilhersteller sind in der Entwicklung ständig bemüht sowohl die Sicherheit und den Komfort des Fahrers also auch der anderen Insassen zu verbessern. Die meisten der entwickelten Systeme sind sowohl zeit- als auch sicherheitskritisch. Einer Studie von Mercedes-Benz zufolge resultieren 80% der Innovationen in der Automobilbranche aus neuen Elektronikkomponenten, deren Funktionen zu 90% durch Software realisiert wird. Um die steigende Komplexität in der Entwicklung von eingebetteten Systemen zu beherrschen wird in der Automobilbranche immer öfter die modelbasierte Softwareentwicklung anstelle der klassischen Programmierung eingesetzt. Im Requirements Engineering, der ersten Phase der Entwicklung eines Produktes, werden die Anforderungen gesammelt und dokumentiert. Die Dokumentation erfolgt mittels natürlicher Sprache. Modellbasierte Ansätze werden heutzutage höchstens unterstützend eingesetzt. Während des Requirements Engineerings muss der Requirements Engineer sowohl die funktionalen Anforderungen an das zu entwickelnde System als auch seine zeitlichen Anforderungen spezifizieren und analysieren. Die funktionalen Anforderungen umfassen dabei insbesondere die Kommunikation zwischen den verschiedenen Teilsystemen. Szenarien stellen eine intuitive Möglichkeit zur Modellierung von funktionalen Anforderungen dar. Im Rahmen dieser Arbeit wird ein modellbasierter Ansatz zur Modellierung von Szenarien verwendet. Anforderungen an das zeitliche Verhalten werden innerhalb der Architektur spezifiziert. Dazu stehen in der Automobilbranche Architekturbeschreibungssprachen wie EAST-ADL zur Verfügung. Obwohl sowohl funktionale als auch zeitliche Anforderungen an das System spezifiziert und analysiert werden müssen, existiert bisher keine Methodik, die beide Ansätze miteinander kombiniert. Aus diesem Grund wurde im Rahmen dieser Arbeit eine neue Requirements Engineering Methodik entwickelt, die eine systematische und ganzheitliche Spezifikation und Analyse der funktionalen und zeitlichen Anforderungen bereitstellt. Wir haben zwei Modelltransformationen entwickelt, um den Requirements Engineer beim Übergang von den funktionalen zu den zeitlichen Anforderungen zu unterstützen. Die vorliegende Arbeit wird durch eine Evaluierung der Methodik, sowie der Modelltransformationen auf Basis eines Komfortsteuergerätes abgerundet.

An optimized photon pair source for quantum circuits - Harder, Georg; Ansari, Vahid; Brecht, Benjamin; Dirmeier, Thomas; Marquardt, Christoph; Silberhorn, Christine (Optics Express)

Theory of quantum frequency conversion and type-II parametric down-conversion in the high-gain regime - Christ, Andreas; Brecht, Benjamin; Mauerer, Wolfgang; Silberhorn, Christine (New Journal of Physics)

Characterizing entanglement in pulsed parametric down-conversion using chronocyclic Wigner functions - Brecht, Benjamin; Silberhorn, Christine (Physical Review A)

An efficient integrated two-color source for heralded single photons - Krapick, S; Herrmann, Harald; Quiring, V; Brecht, Benjamin; Suche, H; Silberhorn, Christine (New Journal of Physics)

Born in the GDR: Imprinting, Structural Inertia and the Survival Chances of Organizations - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (Academy of Management Annual Meeting Proceedings)